ESG practices, mineral resources exploitation and value creation: insights from Chinese mining companies’ digital transformation - Ying-Chieh Lin; Shao-Jun Liu; Li-Sen Zhang (Frontiers in Environmental Science)
IntroductionIn the dynamic landscape of digital technologies, the crucial role of digital transformation in enhancing ESG (Environmental, Social, and Governance) performance, especially concerning the utilization of mineral and fossil fuel resources, has become evident, significantly affecting corporate value. This study aims to explore the relationship between ESG performance and corporate valuation in the Chinese mining industry (especially in high-pollution sectors), as well as the moderating role of digital transformation in this process.MethodsThis study employs a quantitative analysis method, utilizing panel data from Chinese mining companies and conducting regression analysis to examine the relationship between ESG performance, digital transformation, and corporate valuation. We construct a model that includes multiple variables such as resource utilization efficiency, corporate financial conditions, and environmental impact assessments to analyze the pathways through which digital transformation affects resource utilization efficiency and corporate valuation.ResultsThe study finds a significant positive correlation between ESG performance and corporate valuation, meaning that as mineral resource utilization efficiency improves, the market value of the company increases. Digital transformation plays a positive moderating role in this relationship, specifically by enhancing resource utilization efficiency through digital technologies, thereby strengthening ESG performance and ultimately driving up corporate value.DiscussionTherefore, companies should place more emphasis on digital transformation and integrate it with their ESG strategies to improve resource utilization efficiency, thereby enhancing their market competitiveness and long-term value.